2007
DOI: 10.1016/j.brainres.2007.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Chronic morphine treatment up-regulates mu opioid receptor binding in cells lacking filamin A

Abstract: We investigated the effects of morphine and other agonists on the human mu opioid receptor (MOP) expressed in M2 melanoma cells, lacking the actin cytoskeleton protein filamin A and in A7, a sub clone of the M2 melanoma cells, stably transfected with filamin A cDNA. The results of binding experiments showed, that after chronic morphine treatment (24 hr) of A7 cells, MOP binding sites were down-regulated to 63% of control, whereas, unexpectedly, in M2 cells, MOP binding was upregulated to 188% of control naïve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 67 publications
(72 reference statements)
1
12
1
1
Order By: Relevance
“…Even the mechanism of antagonist-induced uporegulation is not yet understood. Our results did provide preliminary evidence that neither increased protein synthesis nor decreased protein degradation appear to play a role, i.e., we saw no change in the density of the MOPr protein band in Western Blots [8].…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Even the mechanism of antagonist-induced uporegulation is not yet understood. Our results did provide preliminary evidence that neither increased protein synthesis nor decreased protein degradation appear to play a role, i.e., we saw no change in the density of the MOPr protein band in Western Blots [8].…”
Section: Discussioncontrasting
confidence: 68%
“…A rather serendipitous finding was reported in a separate paper [8]. While investigating the downregulation of the MOPr in human melanoma cells, we found that in A7 cells chronic morphine induced a modest downregulation of [ 3 H]diprenorphine binding of ca.…”
Section: Upregulation Of Mopr By Chronic Morphine In M2 Cellsmentioning
confidence: 65%
See 2 more Smart Citations
“…Cell membranes from control and DAMGO-treated (5 lM for 24 h) M2, A7 and M2-ABD cells expressing myctagged MOPr were prepared as previously described [7] with some modifications. An aliquot of frozen membranes were diluted in a 50 mM Tris-HCl buffer, pH 7.4, containing 3 mM MgCl 2 , 0.2 mM EGTA, 100 mM NaCl, 10 lM GDP and 10 lg/ml Saponin.…”
Section: [ 35 S]gtpcs Bindingmentioning
confidence: 99%